Activation of the coagulation cascade in severe falciparum malaria through the intrinsic pathway. - Clemens, R; Pramoolsinsap, C; Lorenz, R; Pukrittayakamee, S; Bock, H; White, N (1994)
The mechanisms involved in the activation of the coagulation cascade in severe falciparum malaria were studied in 22 adult patients (19 male, three female) aged 18-45 (mean +/- SD 31 +/- 11) years. Of these, nine had multiple vital organ dysfunction, and bleeding occurred in four patients, two of whom died. During acute illness the reduction in plasma antithrombin III (AT III) concentrations and elevation in thrombin-AT III complexes were associated with significant reductions in factor XII and prekallikrein activities, and an increase in the C1 inhibitor antigen/activity ratio. Serial plasminogen activity remained within the normal range in all patients while protein C activity was significantly reduced. All patients had markedly elevated plasma polymorphonuclear leucocyte elastase (PMN-elastase) levels with mild depletion of alpha-2 macroglobulin but normal concentrations of alpha-1 antitrypsin. There was no correlation between PMN-elastase concentrations and any of the coagulation parameters or concentrations of proteinase inhibitors. These results suggest that the intrinsic pathway of the clotting cascade is activated in severe malaria. This may cause activation of the complement system and release of bradykinin and PMN-elastase and could contribute to the pathogenesis of severe malaria.